2020
DOI: 10.1080/19942060.2020.1774422
|View full text |Cite
|
Sign up to set email alerts
|

Estimating CO2-Brine diffusivity using hybrid models of ANFIS and evolutionary algorithms

Abstract: One of the important parameters illustrating the mass transfer process is the diffusion coefficient of carbon dioxide which has a great impact on carbon dioxide storage in marine ecosystems, saline aquifers, and depleted reservoirs. Due to the complex interpretation approaches and special laboratory equipment for measurement of carbon dioxide-brine system diffusivity, the computational and mathematical methods are preferred. In this paper, the adaptive neuro-fuzzy inference system (ANFIS) is coupled with five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 88 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Therefore, emotion regulation can be effective on psychological toughness. By Increasing the data points the machine learning methods can be used, e.g., [33][34][35][36][37][38][39][40][41][42][43][44]. Therefore, the study on the perception to life and belief system on self-resilience and psychological toughness of cancer patients about the mediating role of emotion regulation can be better investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, emotion regulation can be effective on psychological toughness. By Increasing the data points the machine learning methods can be used, e.g., [33][34][35][36][37][38][39][40][41][42][43][44]. Therefore, the study on the perception to life and belief system on self-resilience and psychological toughness of cancer patients about the mediating role of emotion regulation can be better investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, emotion regulation can be effective on psychological toughness. By Increasing the data points the machine learning methods can be used, e.g., [33][34][35][36][37][38][39][40][41][42][43][44]. Therefore, the study on the perception to life and belief system on self-resilience and psychological toughness of cancer patients about the mediating role of emotion regulation can be better investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results showed that the ANFIS-PSO performance were more superior than ANFIS-DE and conventional ANFIS. Hybridized ANFIS approach was also analyzed in Bemani, Baghban, and Mosavi (2020) , where authors compared and evaluated ANFIS coupled with five different evolutionary algorithms for predicting the diffusivity coefficient of carbon dioxide. ANFIS was hybridized with PSO, GA, ACO, DE and backpropagation (BP) algorithms.…”
Section: Background and Related Workmentioning
confidence: 99%